Enhancing Thai EFL learners' conversation skills through the CA-T Model: a conversation analysis-informed approach - Sinwongsuwat, Kemtong (Frontiers in Education, 2025)
Building on prior research that applies Conversation Analysis (CA) insights to teaching conversation in Thai EFL contexts, this study proposes and evaluates the Conversation Analysis-informed Teaching (CA-T) Model, a novel pedagogical approach to developing EFL learners' conversation skills. A quasi-experimental study was conducted with 12 conveniently sampled Thai EFL teachers (Grade 6: n = 3; Grade 9: n = 5; Grade 12: n = 3; undergraduate: n = 1) and their students across primary, secondary, and tertiary levels in southern Thailand. Teachers received structured training in the CA-T approach before implementing semester-long unit plans with specially developed instructional materials. Students' overall English proficiency and conversational abilities were assessed through pre- and post-instruction direct and indirect tests. Statistical analyses revealed significant improvements across all educational levels (p < 0.01), further supported by positive qualitative feedback from teacher and student group interviews. Teachers expressed a strong intention to continue using the CA-T model in their classrooms, while students reported satisfaction with their conversational achievements. These encouraging results support a systematic national integration of CA insights into EFL speaking curriculum design, empowering learners at all levels to strengthen conversational skills and effectively leverage abundant online recorded talk resources. The findings further suggest that integrating CA principles into English conversation instruction can enhance learners' interactional competence, motivation, and ability to engage with naturalistic spoken English, supporting the potential for broader application of CA-informed pedagogy in EFL contexts through authentic, naturally occurring materials and scaffolded, action-oriented instruction.